Preexisting cardiorespiratory comorbidity does not preclude the success of multidisciplinary rehabilitation in post-COVID-19 patients. (August 2021) - Maniscalco, Mauro; Fuschillo, Salvatore; Ambrosino, Pasquale; Martucci, Michele; Papa, Antimo; Matera, Maria Gabriella; Cazzola, Mario
Abstract: Patients recovering from coronavirus disease 2019 (COVID-19) may not return to a pre-COVID functional status and baseline levels of healthcare needs after discharge from acute care hospitals. Since the long-term outcomes of COVID-19 can be more severe in patients with underlying cardiorespiratory diseases, we aimed at verifying the impact of a preexisting cardiorespiratory comorbidity on multidisciplinary rehabilitation in post-COVID-19 patients. We enrolled 95 consecutive patients referring to the Pulmonary Rehabilitation Unit of Istituti Clinici Scientifici Maugeri Spa SB, IRCCS of Telese Terme, Benevento, Italy after being discharged from the COVID-19 acute care ward and after recovering from acute COVID-19 pneumonia. Forty-nine of them were not suffering from underlying comorbidities, while 46 had a preexisting cardiorespiratory disease. Rehabilitation induced statistically significant improvements in respiratory function, blood gases and the ability to exercise both in patients without any preexisting comorbidities and in those with an underlying cardiorespiratory disease. Response to the rehabilitation cycle tended to be greater in those without preexisting comorbidities, but DLco%-predicted was the only parameter that showed a significant greater improvement when compared to the response in the group of patients with underlying cardiorespiratory comorbidity. This study suggests that multidisciplinary rehabilitation may be useful in post-COVID-19 patients regardless of the presence of preexisting cardiorespiratory comorbidities.